Strategic Autonomy and the EU as a Global Actor: The Evolution, Debate and Theory of a Contested Term - Helwig Niklas; Sinkkonen Ville (Kluwer Law International, 2025)
For all the attention on ‘strategic autonomy’ in the European Union (EU)’s foreign and security policy debate, the academic reflections on the term have so far been limited. Strategic autonomy is a prominent framework through which policy-makers discuss the EU’s response to global challenges, which raises the question to what extent its study can tell us more about the development of the EU as a global actor. This article discusses the evolution of the term ‘strategic autonomy’, the current policy debates that surround it, as well as how its emergence and implications can possibly be analysed through the use of International Relations theory. It argues that strategic autonomy should not be understood as a binary choice between dependence and independence or engagement and decoupling. By accepting the ambiguity of the term and its various meanings in today’s policy debate, it is possible to explore the grey areas of the EU’s struggle to manage its external interdependencies, as well as the implications in diverse policy fields, including foreign policy, security and defence, as well as trade.